Carbon Dioxide Emissions and Business Performance: Firm-level Evidence from Vietnamese Manufacturing Companies - Do, Nhung Hong; Vu, Duy Thai; Tran, Minh Binh; Trinh, Van Mai; Hoang, Ngoc Hong Thi (Journal of Environmental Accounting and Management, 2026)
Vietnam’s intensive industrialization has been a driving force behind its economic growth, creating opportunities for potential expansion of the manufacturing industry. However, the proliferation of manufacturing plants and extensive burning of fuels to support production have posed significant environmental challenges. Recognizing the severe deterioration of ecosystems, Vietnamese enterprises have increasingly committed to mitigating the environmental impacts of manufacturing by integrating sustainability goals into their business strategies. This study empirically examines the relationship between carbon dioxide (CO2) emissions and business performance of Vietnamese manufacturing firms from 2016 to 2022. The findings reveal robust evidence of an inverted U-shaped relationship between CO2 emissions growth and firm performance. Furthermore, the growth rate of CO2 emissions was negatively affected by the COVID-19 pandemic and the financial leverage of Vietnamese manufacturing firms. These results are consistent for both domestic and foreign direct investment (FDI) firms. Notably, larger FDI firms emit fewer pollutants per unit of production than micro-, small-, and medium-sized enterprises (MSMEs), although this difference is not statistically significant for domestic firms. This study provides valuable insights for businesses, offering guidance on optimizing resource utilization, enhancing operational efficiency, and reducing environmental impacts to achieve sustainable industrial development.